Research output of management accounting academics at Universities of Applied Sciences in Germany and Universities of Technology in South Africa: A comparative study of input determinants - Sandra Julia Rosentreter; Penny Singh; Avo Schönbohm (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2013)
German Universities of Applied Sciences and South African Universities of Technology are vocationoriented higher education institutions with a particular focus on applied research. Due to comparable educational tasks and research focus of the institutions in both countries, this paper presents findings of a study that investigated factors influencing research output of management accounting academics in Germany and South Africa. Academics in both countries showed a positive attitude towards research and obtaining postgraduate qualifications. Findings revealed that time available for research, and institutional support systems, influenced academics in both countries. Although there was only a difference of half a unit in the overall average of published articles between the two countries, there were big differences in the publication of articles in accredited and non-accredited journals. – – Deutsche Fachhochschulen und südafrikanische Universities of Technology sind praxisorientierte Hochschulen, die sich auf Anwendungsforschung konzentrieren. Wegen vergleichbarem Bildungsauftrag und gleichem Forschungsfokus der Institutionen in beiden Ländern, beschäftigt sich dieses Paper mit Einflussfaktoren auf die Forschungsaktivität von Controlling Akademikern in Deutschland und Südafrika. Neben Einflussfaktoren, wie z.B. Zeit, Qualifikationsprofil, Struktur der Masterstudiengänge und der persönlichen Einstellung der Akademiker zum Thema Forschung, wurde die Rolle der staatlichen Forschungsförderung beleuchtet. Die Forschungsaktivität deutscher und südafrikanischer Controlling Akademiker wird von ähnlichen Einflussfaktoren bestimmt. Ein großer Unterschied zeigte sich in den Beiträgen von südafrikanischen und deutschen Akademikern zu akkreditierten und nicht akkreditierten Fachzeitschriften.
Keywords: 330